A Triflamide‐Tethered N‐Heterocyclic Carbene–Rhodium(I) Catalyst for Hydroalkoxylation Reactions: Ligand‐Promoted Nucleophilic Activation of Alcohols. Issue 8 (27th March 2017) - Sarbajna, Abir; Pandey, Pragati; Rahaman, S. M. Wahidur; Singh, Kuldeep; Tyagi, Akshi; Dixneuf, Pierre H.; Bera, Jitendra. K.
Abstract: A triflamide‐tethered N‐heterocyclic carbene (NHC)‐bound Rh I dicarbonyl catalyst was highly effective for both intermolecular hydroalkoxylation and intramolecular heteroannulation reactions. The involvement of both the amido nitrogen and triflato oxygen atoms of the triflamide functionality for alcohol activation and 1, 2‐hydrogen shift, respectively, was proposed. Abstract : Alcohol activation : A triflamide‐tethered N‐heterocyclic carbene (NHC)‐bound Rh I (CO)2 catalyst is highly effective for both intermolecular hydroalkoxylation and intramolecular heteroannulation reactions. The involvement of both the amido nitrogen atom and the triflato oxygen atom of the triflamide functionality for alcohol activation and 1, 2‐hydrogen shift, respectively, is proposed. DMAc= N, N ‐dimethylacetamide.